Nocardia niwae Infection in Dogs - Eviny Rodrigues de Oliveira; Joana de Souza Cardoso; Valquíria Tatiele da Silva Rodrigues; Natilene Silva dos Santos; Hellen Thawane Martins Cavalcante; Jeicielly Oliveira dos Santos; João Paulo Vitoria do Nascimento; Alves da Silva Vieira, Layze Cilmara (Acta Scientiae Veterinariae, 2023)
Backgraund: Bacterial dermatopathies are common causes of skin disorders in dogs. The genus Nocardia belongs to the group of aerobic actinomycetes and is responsible for causing disorders in immunosuppressed animals, with cutaneous, subcutaneous, pulmonary or septicaemic manifestations. The present report describes 2 cases of cutaneous nocardiosis, caused by Nocardia niwae in 2 semi-domiciled dogs in the municipality of Barra, BA, Brazil. The emphasis is given to its laboratory, clinical, therapeutic and prognostic analysis. Cases: A 10-month-old male mixed breed (MB) dog (Case 1), was seen at the Veterinary University Hospital of the Federal University of Western Bahia (HVU-UFOB), with a history of bloody diarrhoea, vomiting, lack of appetite and swelling in the submandibular region lasting for 15 days. On physical examination, the animal presented myoclonus in the posterior limbs, motor incoordination and hyperkeratosis in the foot pads. A few days later (Case 2), a 5-month-old male MB dog, from the same domicile, was admitted to the (HVU-UFOB). The main complaint reported was the presence of a nodule on the left side of the thoracic region that had appeared 2 weeks earlier, during the physical examination the presence of a firm nodule was noted, it was adherent and limited to the middle portion of the 6th left rib. In both cases, blood samples for a complete blood count (CBC) and samples of the content of the fistula (Case 1) and nodule (Case 2) were collected by the capillary method and fine needle aspiration puncture (FNAP), for cytological and microbiological examination (respectively). After performing the Matrix Associated Laser Desorption-Ionization - Time MALDI-TOF) technique the pathogen causing the disease in both cases was classified as Nocardia niwae. By evaluating the resistance profile of this bacterium by the disc diffusion method to several classes of antimicrobials, sensitivity was found only to amoxicillin + clavulanate, amikacin, ceftazidime, cefotaxime and meropenem. The drug therapy instituted for animal 1 was based on thymomodulin [Leucogen - 1.8 mg/kg, p.o, SID, 4 mL, during 15 days], Disodium cytidine phosphate, Trisodium uridine triphosphate, Hydroxocobalamin acetate [ETNA - 1 capsule, p.o, BID, during 20 days] and phenobarbital [Gardenal - 2.2 mg/kg, p.o, SID, 10 drops, during 10 days]. This animal died before the results of the cytological and microbiological analyses were available. For animal 2, Cefadroxil [Cefadroxil - 35 mg/kg, dose, p.o, SID, 1 tablet, during 14 days] was used, and also Prednisone [Prednisone - 0.7 mg/kg, p.o, SID, half- tablet, during 6 days], after this application a clinical improvement was noted. Discussion: The macroscopic, microscopic and biochemical characteristics of the bacterium, Nocardia niwae, are in agreement with that cited in the literature. This bacterial species was first identified in a 60-year-old human in 2011, and there are no reports in the literature of infections involving animals. High mortality rates may be associated in part with concomitant diseases with nocardiosis in the case of dog 1, the death may have correlated with canine distemper and the absence of specific treatment for nocardiosis. The early diagnosis of cutaneous nocardiosis and the absence of comorbidities in dog 2, positively influenced the choice of therapy and its clinical cure. These are the first reports of canines naturally infected with Nocardia niwae. Their importance should be emphasised since it is a zoonotic disease. Future studies should be conducted in order to determine the prevalence of the agent in the region of Barra, Western Bahia. Keywords: bacterial diseases, cytology, Nocardia niwae, nocardiosis.